Application of The Discovery Learning Model Assisted by Google Meet to Improve Students' Critical Thinking Skills and Science Learning Outcomes - Mustikaningrum, Galih; Widiyanto, Widiyanto; Mediatati, Nani (International Journal of Elementary Education, 2021)
The Covid-19 pandemic situation has hampered the learning process. This can have a negative effect on the quality of the science learning output. This study aims to describe critical thinking skills and science learning outcomes through the application of the discovery learning model assisted by the Google Meet application. This type of research is Classroom Action Research (PTK) which consists of four stages, namely planning, implementing, observing, and reflecting. The subjects in this study were 15 students. The research instrument used was the critical thinking skills observation sheet and the learning outcome test sheet. The results showed that critical thinking skills in the pre-cycle stage were 52.33, cycle I 60.17, and cycle II 69.17. Then, the completeness of student learning outcomes in the pre-cycle is 60.00%, the first cycle is 73.33%, and the second cycle is 86.67%. Based on this, it can be concluded that learning with the discovery learning model assisted by the Google Meet application can improve critical thinking skills and science learning outcomes. The results of this study have implications for finding solutions to improve the quality of science learning output.